2018
DOI: 10.3892/etm.2018.5909
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of sirtuin 3 protein correlates with early stage chronic renal allograft dysfunction in a rat kidney model

Abstract: Chronic renal allograft dysfunction (CRAD) is the primary factor affecting the long-term survival of patients who have undergone renal transplantation. Oxidative stress and inflammation serve an important role in the pathological damage caused by CRAD in the early post-transplantation phase. Previous studies have demonstrated that sirtuin 3 (sirt3) protects cells from oxidative stress and inflammation. A model of renal orthotopic transplantation was established in the current study and kidney samples were harv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…51 In our previous studies, oxidative stress was also demonstrated by increased levels of MDA, 8-isoprostane, oxidized low-density lipoprotein, and 8-hydroxy-2′-deoxyguanosine; meanwhile, inadequate antioxidant defense was illustrated via decreased levels of the antioxidant enzymes total SOD, catalase, glutathione peroxidase, glutathione reductase, and γ-glutamylcysteine synthetase in CRAD rats. 9,52 Besides, it has been reported that syndecan-1 shedding with GM6001 played renoprotective roles against ischemia-reperfusion injury by phosphorylation of GSK-3β. 53 Consistent with these results, our present study found that the kidney of CRAD rats has increased levels of MDA and decreased levels of SOD.…”
Section: Discussionmentioning
confidence: 99%
“…51 In our previous studies, oxidative stress was also demonstrated by increased levels of MDA, 8-isoprostane, oxidized low-density lipoprotein, and 8-hydroxy-2′-deoxyguanosine; meanwhile, inadequate antioxidant defense was illustrated via decreased levels of the antioxidant enzymes total SOD, catalase, glutathione peroxidase, glutathione reductase, and γ-glutamylcysteine synthetase in CRAD rats. 9,52 Besides, it has been reported that syndecan-1 shedding with GM6001 played renoprotective roles against ischemia-reperfusion injury by phosphorylation of GSK-3β. 53 Consistent with these results, our present study found that the kidney of CRAD rats has increased levels of MDA and decreased levels of SOD.…”
Section: Discussionmentioning
confidence: 99%
“…F344 rat kidneys were orthotopically transplanted into Lewis rats. At 12 weeks following surgery, the kidney expressed a higher level of MDA and lower levels of SOD activity, with increased levels of pathological damaging biomarkers such as serum creatinine levels and the infiltration of tubulointerstitial mononuclear cells, indicating the role of OS in CRAD [62].…”
Section: Chronic Renal Allograft Dysfunction (Crad)mentioning
confidence: 99%
“…F334-to-LEW orthotopic renal transplantation was performed as previously described under a surgical ASX-2 microscope (Shanghai Anxin Optical Instrument Manufacture Co., Ltd., Shanghai, China) [ 19 ]. Rats were anesthetized with 3% sodium pentobarbital (30 mg·kg −1 ) via intraperitoneal injection.…”
Section: Methodsmentioning
confidence: 99%